DYNAMICS OF HIGH-SPEED ELECTRIC LOCOMOTIVE TYPE DS3 - Blokhin, Ye. P.; Pshinko, O. M.; Korotenko, M. L.; Hranovskyi, R. B.; Harkavi, N. Ya.; Dzychkovskyi, E. M. (Science and Transport Progress, 2004)
In paper results of dynamics tests of electric locomotive DS3 are submitted